Dominant Factors Barriers to Hypertension Diet Management in Hypertension Sufferers - Dela Amanda Nisdayanti; Diana Tri Lestari; Ashri Maulida Rahmawati (Universitas Prima Indonesia, 2025)
Hypertension is a serious problem because it causes high morbidity and mortality. One indicator of successful management is diet management. Diet management is often an obstacle for hypertension sufferers. This study aimed to determine the dominant factors that inhibit hypertension diet management in hypertension sufferers in the working area of the Juwana Health Center. This research method used a correlation study with a cross-sectional design. The number of samples in this study was 65 respondents, using a total sampling technique with the inclusion criteria of hypertensive patients who were routinely checked on prolongs, hypertensive patients who implemented hypertension diet management, and hypertensive patients without comorbidities. The instruments used in this research are HKT (Hypertension Knowledge Test), FFQ (Food Frequency Questionnaire), FFS (Family Support Scale), PSS (Perceived Stress Scale), and HSMBQ (Hypertension Self Management Behavior Questionnaire). Data analysis used chi-square and simple logistic regression. The results of data analysis show that hypertension diet management is affected by knowledge (p: 0.003, OR: 2.764), dietary habits (p: 0.001, OR: 7.986), income (p: 0.004, OR: 2.098), family support (p: 0.001, OR: 9.986), and stress (p: 0.001, OR: 3.874). The most dominant factors are family support (p: 0.001, OR: 9.986, 95% CI: 0.653 < OR < 23.98). Family support is the most dominant factor affecting hypertension diet management. Positive system support is necessary for the patient's success in controlling blood pressure. Conclusion: There are factors that affected diet management of the hypertension: knowledge, dietary patterns, income, family support, and stress, with the dominant factor being family support.